Effects of pain Scrambler therapy for management of burn scar pruritus: A pilot study. Issue 3 (May 2017) - Joo, So Young; Cho, Yoon Soo; Cho, Sung-Rae; Kym, Dohern; Seo, Cheong Hoon
Highlights: We investigated the effects of pain Scrambler therapy on burn scar pruritus. The numerical rating scale, 5-D Itch Scale, and Leuven Itch Scale were evaluated. Scrambler therapy is a non-invasive modality that significantly reduced burn pruritus. Abstract: Purpose: Pain Scrambler therapy is a patient-specific electrocutaneous nerve stimulation device. Burn pruritus is a common form of chronic and disabling neuropathic pain that is often difficult to treat effectively. Pruritus is mediated by histamines, which are effector molecules stored in mast cells and released locally during injury or inflammation. Burn pruritus may be accompanied by peripheral neuropathic pain, which may result from injury to sensory nerves that hampers conductance of neuronal messages along the large A and small C afferent fibers to the spinal cord. In this study, we investigated the effect of pain Scrambler therapy on burn scar pruritus. Methods: Sixteen subjects were recruited to participate in this study. The subjects complained of severe pruritus that was rated at least 5 on the visual analogue scale (VAS), despite treatments with antihistamines, gabapentin medication, and other physical modalities. Each Scrambler Therapy with the MC-5A Pain Scrambler Therapy ® technology device was performed for 40 min daily (Monday through Friday) for 10 consecutive days. The stimulus was increased to the maximum intensity bearable by the individual patient without causing any additional pain or discomfort. The numerical rating scale (NRS), 5-D Itch Scale, and Leuven Itch Scale were administered and evaluated immediately before Scrambler therapy, and then immediately after 5 and 10 therapy sessions. Results: For all 16 patients, NRS showed mean values of 6.75 ± 1.13 before therapy, 5.06 ± 1.53 after 5 sessions, and 4.13 ± 1.45 after 10 sessions. The NRS values before therapy and after 10 sessions were significantly different (p < 0.05). Pruritus frequency, severity, and consequences scores on the Leuven Itch Scale after Scrambler therapy were also significantly different (p < 0.05). Duration, degree, direction, and disability scores on the 5-D Itch Scale were also significantly different (p < 0.05). Conclusions: Scrambler therapy is a non-invasive, non-medicinal modality that significantly reduced burn-associated pruritus. Scrambler therapy should be considered as a treatment option for burn survivors with severe pruritus.